A new burmagomphid dragonfly from the Eocene of Patagonia, Argentina - Petrulevicius, Julian Fernando (2017)
A new burmagomphid anisopteran, Satelitala soberana gen. et sp. nov. is described from the lower Eocene of Laguna del Hunco, Patagonia, Argentina. The new genus is characterised by hindwing characters such as the subdiscoidal triangle not elongated; anal loop divided longitudinally; paranal cell divided longitudinally; five terminal cells between RP and MA; five terminal cells between MP and CuA; and obtuse angle between PsA and CuP+AA. Burmagomphid dragonflies were represented so far only by one specimen from the middle Cretaceous of Southeast Asia. This new record extends the distribution to Patagonia, to the Cenozoic, and also to paleolake deposits.